SYNTACTIC CATEGORIES AND TYPES: AJDUKIEWICZ AND MODERN CATEGORIAL GRAMMARS. - Buszkowski, Wojciech (Poznan Studies in the Philosophy of the Sciences & the Humanities, 2015)
This essay confronts Ajdukiewicz's approach to syntactic categories with modern categorial grammars, mainly AB-grammars (basic categorial grammars) and Lambek grammars, i.e. categorial grammars based on different versions of the Lambek calculus.